2014
DOI: 10.1111/ggi.12237
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Cantonese Chinese Montreal Cognitive Assessment in Southern Chinese

Abstract: The Cantonese Chinese MoCA is a consistent and reliable instrument. In terms of its validity, the MoCA is better in the detection of AD than aMCI in Cantonese-speaking Chinese persons. It is only fair for the screening of aMCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 13 publications
4
56
2
1
Order By: Relevance
“…The RUDAS score of 23 also correlates with its cut‐off for screening for cognitive impairment. This is not the case with the MoCA, though other studies have suggested a lower cut‐off for screening of cognitive impairment . While the MoCA has been shown in previous studies to correlate with the discharge FIM, in this study there was a poor correlation between the RUDAS and discharge FIM.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The RUDAS score of 23 also correlates with its cut‐off for screening for cognitive impairment. This is not the case with the MoCA, though other studies have suggested a lower cut‐off for screening of cognitive impairment . While the MoCA has been shown in previous studies to correlate with the discharge FIM, in this study there was a poor correlation between the RUDAS and discharge FIM.…”
Section: Discussioncontrasting
confidence: 86%
“…While the MoCA is influenced by education, even when adjusted for educational level, there was a four point difference average between MoCA scores in NESB and English‐speaking participants, despite no significant differences in RUDAS scores between both groups. While this does not rule out a larger group of undiagnosed cognitive impairment in the NESB cohort, given the similar RUDAS scores between both language groups, this suggests that despite the MoCA being written in the preferred language, language may still impact on scoring . This is important as many patients with cognitive impairment may revert to their primary language, so testing them using the correct language is necessary.…”
Section: Discussionmentioning
confidence: 94%
“…Proper diagnosis rates in previous cross‐sectional studies using the Montreal Cognitive Assessment, which is considered suitable for the screening of MCI, are comparable with our value (i.e. 0.64–0.92) . Considering that the MCIS is an index that does not include the examination of cognitive function (for example, the MMSE), it can be considered acceptable.…”
Section: Discussionsupporting
confidence: 74%
“…Because there is much geographic and cultural variability across China, specific regional characteristics may influence the performance of local residents on these neuropsychological tests. For example, the word “church” used in the delayed recall of MoCA was directly translated in the Beijing version, whereas it was replaced by “temple” in the Cantonese version, because the translator of the Cantonese version thought that “temple” was more familiar than “church” to Chinese older adults . These different words affected the difficulty of delayed recall, which might affect the validity and reliability of these versions of MoCA .…”
Section: Discussionmentioning
confidence: 99%
“…There are subtle differences between these versions in the stimuli and materials used in the TMT, verbal fluency, delayed recall, abstraction, and naming tests. Adjustment for level of education and cutoff scores for MCI were also different in each of these versions . In clinical practice, these differences between the various Chinese MoCA versions may increase the possibility of false positives and thus lower the validity of Chinese versions of the MoCA .…”
mentioning
confidence: 99%